Gut microbe metabolism of small molecules supports human development across the early stages of life - Tarracchini, Chiara; Fontana, Federico; Mancabelli, Leonardo; Lugli, Gabriele Andrea; Alessandri, Giulia; Turroni, Francesca; Ventura, Marco; Milani, Christian (Frontiers in Microbiology, 2022)
From birth to adulthood, the human gut-associated microbial communities experience profound changes in their structure. However, while the taxonomical composition has been extensively explored, temporal shifts in the microbial metabolic functionalities related to the metabolism of bioactive small molecules are still largely unexplored. Here, we collected a total of 6617 publicly available human fecal shotgun metagenomes and 42 metatranscriptomes from infants and adults to explore the dynamic changes of the microbial-derived small molecule metabolisms according to the age-related development of the human gut microbiome. Moreover, by selecting metagenomic data from 250 breastfed and 217 formula-fed infants, we also investigated how feeding types can shape the metabolic functionality of the incipient gut microbiome. From the small molecule metabolism perspective, our findings suggested that the human gut microbial communities are genetically equipped and prepared to metabolically evolve toward the adult state as early as one month after birth, although at the age of four years, it still appeared functionally underdeveloped compared to adults. Furthermore, in respect of formula-fed newborns, breastfed infants showed enrichment in microbial metabolic functions related to specific amino acids present at low concentrations in human milk, highlighting that the infant gut microbiome has specifically evolved to synthesize bioactive molecules that can complement the human breast milk composition contributing to complete nutritional supply of infant.